Seven cases of parathyroid carcinoma and review of the literature - YAVUZ, DİLEK (SPRINGER INTERNATIONAL PUBLISHING AG, 2021)
Parathyroid cancer is a rare malignancy and an uncommon cause of hyperparathyroidism. In the present study, we present seven cases of parathyroid carcinoma. The female ratio was 5/7 (71.4%). Median age at diagnosis was 47 years, and median follow-up duration was 60 months (IQR 29-75). Mean calcium level at diagnosis was 12.7 mg/dL (range, 11.3-13.9), and mean parathormone level was 1115 ng/L (IQR 287-1470). Two patients (28.5%) had a palpable neck mass. Coexisting brown tumor was present in three patients (42.8%), and nephrolithiasis was found in one patient (14.2). Average tumor size was 29 mm (IQR 28-40). Capsular and vascular invasion were detected in six patients (85.7%), intrathyroidal spread was observed in two patients (28.5%), and soft tissue invasion was seen in three patients (42.8%). Parathyroid adenoma was present in one patient and parathyroid gland hyperplasia in another patient. Adjuvant radiotherapy was given to four patients (57.1%). There was no metastatic disease or death. At the last visit, two patients had increased parathormone levels and no additional focus could be detected in either. Patients with markedly elevated parathormone and calcium levels and a palpable larger mass on the neck should be evaluated for parathyroid cancer. En bloc resection is the mainstay treatment. Despite contradictory results, adjuvant radiotherapy to the neck may help to reduce the risk of local recurrence in patients with microscopic residual parathyroid carcinoma.
Keywords: Hypercalcemia; Hyperparathyroidism; Parathyroidectomy; Parathyroid carcinoma; DIAGNOSIS; UPDATE; FEATURES; CANCER